PENJAMIN MUTU PENDIDIKAN GURU BIMBINGAN KONSELING DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN (SMK) - Purnama, Diana Septi (MAJALAH ILMIAH PEMBELAJARAN, 2011)
In the constellation of global education one of the vital areas of the field of guidance and counseling. Strategis strata occupy this area as a mainstay of the global competitive ability of a country because it is closely related to human resource development hegemony superior schools in a variety of scales. Guidance and counseling field related to quality have logical consequences that are very heavy, because it must work in both worlds. Campus as a center of education, training, personality development, management ability and communication skills. On the other hand, graduates/school counselor produced by LPTK to be completely coherent, insight and eligible with the existing school environment. Based on the thought of two things above the field of guidance and counseling specifically for teacher education pattern which should be developed is set multy entry-exit system model. This model puts environmental school as an integral part in the learning process, so it will act as a technical academic wider laboratory. And process quality guarantee automatically attached directly to the user that is educational industry itself.